Analgesic Effects of Different κ-Receptor Agonists Used in Daytime Laparoscopic Cholecystectomy. (29th December 2021) - Zhou, Wanjun; Wang, Jiawu; Hu, Chengyun; Dai, Feibiao; Zhang, Zhetao; Li, Chuanyao; Tang, Chaoliang; Xie, Yanhu
Abstract : Background . Comparing the effect of two different κ -receptor agonists, nalbuphine and oxycodone, and regular morphine in patients for prophylactic analgesia of acute pain after daytime laparoscopic cholecystectomy. Methods . One hundred and twenty-four patients undergoing laparoscopic cholecystectomy were randomly allocated to receive nalbuphine (group N), oxycodone (group O), and morphine (group M). The three groups were all given intravenous injection (iv.) of 0.15 mg/kg injection before incision and 0.05 mg/kg injection at the end of pneumoperitoneum. The Visual Analogue Scale (VAS) scores (incision, visceral, and shoulder) and Ramsay sedation scores at 1, 2, 4, 8, 12, 16, 20, and 24 hours after surgery, the time of extubation, the incidence of postoperative adverse events, the satisfaction of pain treatment, and the duration of stay after surgery were all recorded. Results . Compared with group M, the VAS scores of visceral pain at rest decreased in group N and group O at 1-8 h after surgery (P < 0.05 ). The VAS scores of visceral pain at movement in group N decreased longer than those in group O (P < 0.05 ). Compared with that of group M, the postoperative time in Ramsay sedation score of group O increased longer than that of group N (P < 0.05 ). Compared with group N, patients had worse sleep quality in group O, longer length of stay in group M, and lower satisfaction in both groups. Conclusion . Compared with morphine, prophylactic use of the κ -receptor agonists, nalbuphine and oxycodone, during laparoscopic cholecystectomy can reduce postoperative visceral pain. Furthermore, the nalbuphine group had fewer adverse reactions, better analgesia, and better satisfaction.